Interplay between bile acid metabolism and microbiota in irritable bowel syndrome. Issue 9 (5th April 2016) - Dior, M.; Delagrèverie, H.; Duboc, H.; Jouet, P.; Coffin, B.; Brot, L.; Humbert, L.; Trugnan, G.; Seksik, P.; Sokol, H.; Rainteau, D.; Sabate, J.‐M.
Abstract: Background: Irritable bowel syndrome (IBS) physiopathology is multifactorial and roles for both microbiota and bile acid (BA) modifications have been proposed. We investigated role of dysbiosis, transit pattern and BA metabolism in IBS. Methods: Clinical data, serum, and stool samples were collected in 15 healthy subjects (HS), 16 diarrhea‐predominant (IBS‐D) and 15 constipation‐predominant IBS (IBS‐C). Fecal microbiota composition was analyzed by real‐time PCR. Sera and fecal BA profiles, 7 α ‐C4 levels, and in vitro BA transformation activity by fecal microbiota were measured by mass spectrometry. Serum Fibroblast Growth Factor 19 (FGF19) was assayed by ELISA. Keys Results: Dysbiosis was present in IBS patients with an increase in Escherichia coli in IBS‐D patients ( p = 0.03), and an increase in Bacteroides ( p = 0.01) and Bifidobacterium ( p = 0.04) in IBS‐C patients. Sera primary and amino‐conjugated BA were increased in IBS‐D (63.5 ± 5.5%, p = 0.01 and 78.9 ± 6.3%, p = 0.03) and IBS‐C patients (55.9 ± 5.5%, p = 0.04 and 65.3 ± 6.5%, p = 0.005) compared to HS (37.0 ± 5.8% and 56.7 ± 8.1%). Serum 7 α ‐C4 and FGF19 levels were not different among all three groups. Fecal primary BA were increased in IBS‐D patients compared to HS, including chenodeoxycholic acid which has laxative properties (25.6 ± 8.5% vs 3.5 ± 0.6%, p = 0.005). Bile acid deconjugation activity was decreased in IBS‐D ( p = 0.0001) and IBS‐C ( p = 0.003) feces. Abdominal pain was positively correlated with serum ( R = 0.635, p < 0.001) and fecal ( R = 0.391, p = 0.024) primary BA. Conclusions & Inferences: Different sera and fecal BA profiles in IBS patients could be secondary to dysbiosis and further differences between IBS‐C and IBS‐D could explain stool patterns. This study opens new fields in IBS physiopathology and suggests that modification of BA profiles could have therapeutic potential. Abstract : We demonstrated that in comparison to healthy subjects, IBS patients have different serum and fecal bile acid profiles that could be secondary to dysbiosis and altered metabolic functions. We also observed variation in bile acid profiles between IBS‐C and IBS‐D patients, which may explain differences in stool patterns. Bile acid profiles were also correlated with abdominal pain.